Crossing Boundaries and Time: An Exploration of Time Allocation, Emotional Well-Being of Immigrants in the United States - Nicola Daniele Coniglio; Rezart Hoxhaj; Raffaele Lagravinese (Global Labor Organization (GLO), 2023)
This study investigates the emotional experiences of immigrants and native- born individuals in the United States, exploring the relationship between daily activities and feelings of happiness, stress, and meaningfulness. We analyze the entire range of daily activities and their durations, utilizing data from the American Time-Use Survey (ATUS) Well-Being modules. The results reveal that when viewed through the evaluation lenses of the general US population, immigrants engage in less happy, more stressful, and less meaningful activ- ities compared to natives. However, when considering subjective emotional assessments, immigrants are more optimistic and perceive these activities as associated with higher levels of happiness and meaningfulness. The study also finds evidence of emotional assimilation over time, with happiness disparities between immigrants and natives diminishing. However, this process appears incomplete for second-generation immigrants. The findings highlights the im- portance of recognizing the different perspectives of immigrants to formulate inclusive policies that facilitate integration.
Keywords: J15; J22; I31; Z13; 330; Immigrants; TimeUse; Emotional Experiences; Assimilation; Well-Being